2011
DOI: 10.1590/s0102-695x2011005000151
|View full text |Cite
|
Sign up to set email alerts
|

Contribution for the phytochemical studies of Ageratum fastigiatum

Abstract: Organic extracts from leaves plus branches plus inflorescences of Ageratum fastigiatum (Gardner) R. M. King & H. Rob., Asteraceae, were fractionated through classic chromatography. The steroids stigmasterol, chondrillasterol and campesterol were isolated from hexane extract. The triterpenes lupeol, taraxasterol, α-amyrin, β-amyrin, pseudotaraxasterol, lupeol acetate and α-amyrin acetate were isolated from ethyl acetate extract. Steroids and triterpenes were identified by GC-MS. The coumarin ayapin was isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…In this context, although antinociceptive and anti-inflammatory activities of A. fastigiatum had been previously described by our research group, this is the first report to establish a full scientific understanding for medicinal use of the branches, an important part of this plant widely used as extract by population after maceration (Gonçalves et al 2011). Therefore, in the present study, the antioxidant, antinociceptive and anti-inflammatory properties of the ethanol extract from A. fastigiatum branches using appropriate experimental animal models were investigated.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…In this context, although antinociceptive and anti-inflammatory activities of A. fastigiatum had been previously described by our research group, this is the first report to establish a full scientific understanding for medicinal use of the branches, an important part of this plant widely used as extract by population after maceration (Gonçalves et al 2011). Therefore, in the present study, the antioxidant, antinociceptive and anti-inflammatory properties of the ethanol extract from A. fastigiatum branches using appropriate experimental animal models were investigated.…”
mentioning
confidence: 70%
“…The branches of this species are indicated in traditional medicine as cicatrizing, anti-inflammatory, analgesic and antimicrobial (Del-Vechio-Vieira et al 2008). Phytochemical studies have identified diterpenes, triterpenes, steroids, coumarins and derivatives (Gonçalves et al 2011, Del-Vechio et al 2007, Bohlmann et al 1981, 1983. The main compounds found in the essential oil were α-pinene, limonene, germacrene D, α-humulene and β-cedrene (Gonçalves et al 2011, Del-VechioVieira et al 2009a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated RRIs were compared with those observed for a series of terpene standards, as described in the literature (Gonçalves et al, 2011). The terpene standards used were previously isolated from extracts of various plants and identified by 1 H-NMR and 13 C-NMR (presented good degree of purity) and are deposited at the Núcleo de Pesquisa em Produtos Naturais e Sintéticos, da Faculdade de Ciências Farmacêuticas de Ribeirão Preto -USP (SP, Brazil).…”
Section: General Experimental Proceduresmentioning
confidence: 99%
“…In Brazil Ageratum fastigiatum is also known as "matapasto" or "enxota" and aqueous extracts are used to treat pain and inflammations (GONÇALVES et al, 2011). Substances that were isolated from this species include triterpenes, diterpenes, coumarin, eudesmane derivatives, labdane derivatives and steroids (see Table 8).…”
Section: Chemical Constituents Of the Genus Vernoniamentioning
confidence: 99%